Olive's ocean - Henkes, Kevin. (Greenwillow Books, 2003)
On a summer visit to her grandmother's cottage by the ocean, twelve-year-old Martha gains perspective on the death of a classmate, on her relationship with her grandmother, on her feelings for an older boy, and on her plans to be a writer.